PENGARUH UKURAN DEWAN KOMISARIS DAN PROPORSI KOMISARIS INDEPENDEN TERHADAP KINERJA KEUANGAN DENGAN MANAJEMEN LABA SEBAGAI VARIABEL INTERVENING - Akhmad Afnan; Rahardja Rahardja (Diponegoro Journal of Accounting, 2014)
Agency conflicts can create earnings management that will ultimately lead to poor quality of corporate earnings. It can be seen from the many cases of corporate accounting reporting scandals that occurred in Indonesia. The objective of this study is to test the effect of corporate governance on earnings management and its influence on financial performance. The population in this study is all the companies in the manufacturing sector on the Indonesia Stock Exchange, with the financial statements from 2010 to 2012. This study is a quantitative study using multiple regression analysis and simple regression. Multiple regression analysis is used to test the effect of corporate governance of earnings management, while the simple regression is used to test the effect of earnings management on financial performance. This study used Modified Jones, which is a program used to analyze earnings management. The results showed that board of director have a positive impact on earnings management, while the proportion of independent board and board of comissioner showed no significant effect on earnings management. Related to the performance of the company, based on the analysis conducted it could be concluded that the effect of earnings management on the performance of the financial, such as a significant positive effect increasing earnings management.